2002
DOI: 10.2460/javma.2002.221.995
|View full text |Cite
|
Sign up to set email alerts
|

Influence of vestibulovaginal stenosis, pelvic bladder, and recessed vulva on response to treatment for clinical signs of lower urinary tract disease in dogs: 38 cases (1990-1999)

Abstract: Vestibulovaginal stenosis is likely an important factor in dogs with vestibulovaginal ratio < 0.20. Vaginectomy or resection and anastomosis should be considered in dogs with severe vestibulovaginal stenosis and signs of lower urinary tract disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
19
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(21 citation statements)
references
References 7 publications
0
19
0
Order By: Relevance
“…3 Vestibulovaginal stenosis has been suggested to result in recurrent urinary tract infections, chronic vaginitis, vulvar dermatitis, increased frequency of micturition, incontinence, and mating difficulties. 1,4,5 The degree of constriction at the vestibulovaginal junction necessary to be considered abnormal or to contribute to clinical signs is unclear. Even though there has not been a normal population of dogs studied, the current literature states that the normal vestibulovaginal junction should be larger than a third of the diameter of the vagina.…”
mentioning
confidence: 99%
See 3 more Smart Citations
“…3 Vestibulovaginal stenosis has been suggested to result in recurrent urinary tract infections, chronic vaginitis, vulvar dermatitis, increased frequency of micturition, incontinence, and mating difficulties. 1,4,5 The degree of constriction at the vestibulovaginal junction necessary to be considered abnormal or to contribute to clinical signs is unclear. Even though there has not been a normal population of dogs studied, the current literature states that the normal vestibulovaginal junction should be larger than a third of the diameter of the vagina.…”
mentioning
confidence: 99%
“…6 Another measurement guideline used to determine the normal size of the vestibulovaginal junction is called the vestibulovaginal ratio. 5 This ratio is calculated by dividing the height of the vestibulovaginal junction by the maximum height of the vagina on a lateral vaginourethrogram. 5 Dogs with vestibulovaginal ratios ,0.33 to 0.35 are considered to have vestibulovaginal stenosis.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…7 It has been previously reported that the vestibulovaginal junction should be larger than one-third of the diameter of the vagina. 1 To our knowledge, no filling pressure for performing vaginourethrography for any mammalian species has been described in the veterinary medical literature. A study 8 involving spayed dogs with and without lower urinary tract signs revealed no significant cutoff point in the vestibulovaginal ratio with which to differentiate clinically affected dogs from unaffected dogs.…”
Section: Discussionmentioning
confidence: 99%